ANALYSIS OF CHANGES IN THE PARAMETERS OF THE MATURATION OF SREMSKI SAUSAGE WITH PREVIOSLY GIVEN TEHNICAL CHARACTERISTICS OF THE CHAMBER - Jovanovska, V.; Kuzelov, A. (Journal of Engineering & Processing Management, 2012)
Srem sausage belongs to the group of durable delicatessen products whose production is known since a long time ago. It is produced by selected recipe at precisely determined tehnical characteristics of the maturation chamber. The change of relative humidity, air temperature during the maturation and changes of pH values in the stuffing mass has been analyzed Also the difference in the mass of the Srem sausage has been determined at the begining and the end of maturation. The bacteriological state and organoleptic characteristics are examined.The processed data of changes are given in a tabular display.